2013 IEEE Congress on Evolutionary Computation 2013
DOI: 10.1109/cec.2013.6557834
|View full text |Cite
|
Sign up to set email alerts
|

Toward a hybrid approach to generate Software Product Line portfolios

Abstract: Software Product Line (SPL) development is a new approach to software engineering that aims at the development of a whole range of products. One of the problems which hinders the adoption of that approach is related with the management of the products of the line. Additionally, the scope of a software product line is determined by the bounds of the capabilities provided by the collection of products in the product line. This introduces new challenges related to the scope problem. One of the main three differen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
5
2
2

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 13 publications
0
9
0
Order By: Relevance
“…Cruz et al [36] use a hybrid approach, which combines fuzzy inference systems and the well-known multi-objective genetic algorithm, NSGAII, to help decision makers manage product lines by generating portfolios of products. These portfolios are based on user segments and the development cost of SPL products.…”
Section: Search Based Feature Model Selectionmentioning
confidence: 99%
“…Cruz et al [36] use a hybrid approach, which combines fuzzy inference systems and the well-known multi-objective genetic algorithm, NSGAII, to help decision makers manage product lines by generating portfolios of products. These portfolios are based on user segments and the development cost of SPL products.…”
Section: Search Based Feature Model Selectionmentioning
confidence: 99%
“…• Inferring: use of functional metrics to a static or runtime quantifiable measurement of NFPs [9,27,29,31], which allows the detection of interactions resulting from a valid set of features. We assume that implicitly and inferring NFPs were previously specified by using state-of-the-art techniques.…”
Section: Contextual Modelingmentioning
confidence: 99%
“…We assume that implicitly and inferring NFPs were previously specified by using state-of-the-art techniques. For instance, Cruz et al [9] and Zanardini et al [31] infer NFPs based on a rigorous static source code inspection, e.g., analysis of coupling and cyclomatic complexity. In this case, the success of implicitly specifying or inferring NFPs depends very significantly on the quality of such techniques, and it also varies considerably across different systems.…”
Section: Contextual Modelingmentioning
confidence: 99%
“…Sayyad found that the combination of the PUSH and PULL methods worked well for smaller models but performed poorly when applied to the Linux kernel model. Cruz et al [Cruz et al 2013] proposed using many-objective optimisation for the generation of SPL product portfolios. For the evaluation of their work, they used the NSGA-II algorithm for the selection of products minimising cost and maximising user relevance on a library management case study with 23 features and 4 attributes per feature.…”
Section: Many-objective Optimisationmentioning
confidence: 99%